METHODS OF EFFECTIVE USE OF ICT TOOLS IN THE TEACHING OF NATURAL SCIENCES - Mirzabekova, Gumshagul Khodzhabekovna (SCIENCE and SOCIETY, 2026)
Using ICT tools in teaching natural sciences increases students’ interest, develops independent thinking, and ensures lesson effectiveness. This article discusses the relevance of using ICT in the classroom, the types of tools applied, their role in improving students’ knowledge, and the importance of teacher competence. It also explores effective teaching methods using multimedia resources, virtual labs, and interactive tests. The findings demonstrate the key role of ICT in teaching natural sciences with a modern approach.
Keywords: natural sciences; ICT; digital technology; teaching methods; virtual lab; multimedia; interactive lesson; lesson effectiveness; student activity; independent thinking; modern education; teacher competence